Synthesis, Characterization with Photophysical and Ion Binding Properties of Ruthenium Complex - Kong, Jian-Fei; Wang, Yu-Jie; Liu, Lu; Shi, Guang-Jun; Lang, Hui-Zhen; Zhang, Chun-Hua (Asian Journal of Chemistry, 2015)
Host-guest chemistry has attracted much attention in the past several decades and the design of highly selective and sensitive receptors for metal ions is of great importance in the area of ion transport, chemosensing, biomedical as well as environmental applications. Herein we report the synthesis, photophysics and ion-binding studies of new ruthenium(II) 2,2'-bipyridine complex containing crown pendants. The binding constants of the complex for different metal ions were determined by UV-visible absorption.